Empowerment of PT. MSEs/Individual for Participating in Government Procurement of Goods and Services - Sandy Hukunala; Adolof Seleky (Dialogia Iuridica, 2023)
The obstacles faced by micro, small, and medium enterprises (MSMEs) in participating in public procurement even though they are legal entities are related to the system, culture, and human resources implementing public procurement. The first obstacle is Indonesia's rigid and inflexible public procurement system. The qualification requirements set by the government often do not match the capabilities of MSMEs. In addition, the lack of internet network access support in the regions makes it difficult for MSMEs to participate in the procurement of goods and services. The second obstacle is the culture of corruption, collusion, and nepotism (KKN) that is still inherent in the Indonesian bureaucracy. Goods and services procurement is one of the biggest contributors to corruption cases in Indonesia. The third barrier is the limited human resources, both in terms of numbers and competencies, owned by MSMEs. MSMEs often have inadequate quality of human resources, especially in terms of knowledge and skills in the field of goods and services procurement. The research method used is normative juridical with a statutory approach and conceptual approach. The purpose of this research is to find out what causes MSEs to be difficult to participate in the procurement of government goods and services even though they are legal entities. This research is expected to contribute to the development and improvement of the public procurement system, so that in practice it can involve more micro, small, and medium enterprises, especially those that already have legality and meet technical requirements.